Biomaterials Used for Periodontal Disease Treatment: Focusing on Immunomodulatory Properties - Garzón, H.; Suárez, L. J.; Muñoz, S.; Cardona, J.; Fontalvo, M.; Alfonso-Rodríguez, C. A. (International Journal of Biomaterials, 2022)
The growing use of biomaterials with different therapeutic purposes increases the need for their physiological understanding as well as to seek its integration with the human body. Chronic inflammatory local pathologies, generally associated with infectious or autoimmunity processes, have been a current therapeutic target due to the difficulty in their treatment. The recent development of biomaterials with immunomodulatory capacity would then become one of the possible strategies for their management in local pathologies, by intervening in situ, without generating alterations in the systemic immune response. The treatment of periodontal disease as an inflammatory entity has involved the use of different approaches and biomaterials. There is no conclusive, high evidence about the use of these biomaterials in the regeneration of periodontitis sequelae, so the profession keeps looking for other different strategies. The use of biomaterials with immunomodulatory properties could be one, with a promising future. This review of the literature summarizes the scientific evidence about biomaterials used in the treatment of periodontal disease.